Petrogenesis of the Cretaceous Zhangzhou batholith in southeastern China: Zircon U–Pb age and Sr–Nd–Hf–O isotopic evidence - Chen, Jing-yuan; Yang, Jin-hui; Zhang, Ji-heng; Sun, Jin-feng; Wilde, Simon (Elsevier BV, 2013)
Whole-rock geochemical and Sr–Nd–Hf isotopic data and in situ zircon U–Pb and Hf–O isotopes have been determined for mafic (gabbro and diorite) and felsic (I- and A-type granites) rocks from the Zhangzhou batholith in southeastern (SE) China, in order to constrain their source and petrogenesis. The batholith consists of gabbro, diorite, granodiorite, monzogranite and alkali feldspar granite, with mafic microgranular enclaves in the monzogranite. Zircon SIMS and LA–ICP–MS U–Pb dating gives consistent emplacement ages of 107–97 Ma for these rocks, establishing that the mafic and felsic magmas were coeval. The gabbros and diorites have relatively high MgO contents (up to 5.2 wt.%) at low silica concentrations (up to 49.9 wt.%), with relatively homogeneous whole-rock initial 87Sr/86Sr ratios (~ 0.706), negative εNd(t) values of − 3.4 to − 2.7, chondrite-like εHf(t) values of − 0.3 to + 0.5, zircon εHf(t) values of − 0.8 to + 3.2 and δ18O values of + 5.0 to + 6.1‰, indicating that they were derived by partial melting of an enriched subcontinental lithospheric mantle, coupled with olivine and pyroxene fractionation.The calc-alkaline granodiorites and monzogranites are metaluminous and have relatively high SiO2 and low MgO contents. They have whole-rock initial 87Sr/86Sr ratios of 0.706, εNd(t) ratio of − 3.0 to − 4.0, εHf(t) values of − 2.0 to + 0.3 and zircon εHf(t) values of − 4.4 to + 0.3, with Nd and Hf model ages of about 1.3 Ga, indicating that they were mainly derived by partial melting of old continental crustal materials. The alkali feldspar granites have geochemical features similar to A-type granite, with relatively high K2O + Na2O and Nb contents and FeO/MgO and Ga/Al ratios. They have distinct isotopic compositions from the associated mafic rocks, with εNd(t) values of − 4.9, εHf(t) values of − 3.2 to − 3.5, zircon εHf(t) values of − 5.1 to + 1.0 and δ18O values of + 5.1‰ to + 6.3‰. They are depleted in Sr, Ba and Eu, indicating that they were mainly derived from partial melting of crustal materials with plagioclase in the residue. Field observations, as well as the petrographic and geochemical data, suggest that the mafic and felsic rocks in the Zhangzhou batholith- were the result of mixing between lithospheric mantle-derived and crustally-derived magmas, coupled with crystal fractionation, in an extensional setting related to Cretaceous subduction of the Paleo-Pacific Plate.